Reflection on the Teaching Path of International Law under the Background of “Anti-globalization” - Xu, Panya (Pacific International Journal, 2024)
The main goal of international law teaching is to help students improve their ability to understand the connotation of macro international law, understand the historical evolution of middle international law system, grasp the norms of micro international law and analyze international affairs. Under the background of “anti-globalization”, although the content of international law curriculum has not changed substantially, its value is easily alienated by external influences. On the one hand, “anti-globalization” will intensify the political bias of international law, weaken its legal attribute, cause students to question the effectiveness of international law, and then generate the “useless” attitude of international law; On the other hand, “anti-globalization” ignores the multi-value connotation of international law, tends to emphasize the instrumental value of international law, and imperceptibly affects students’ cognition of the value of international law, and reduces the positive effect of international law teaching. Based on this, this paper holds that, teachers should actively innovate the teaching path of international law, and under the guidance of the concept of multilateralism, increase the theoretical output in the teaching of international law, help students further acknowledge the multilateral characteristics of international law, thus overcoming the negative influence brought by “anti-globalization”.